Medication-Focused Patient Counseling Upon Discharge: A Feasibility Study of Effect on Patient Satisfaction - Carina Lundby; Julia Filipsen; Susanne Rasmussen; Anton Pottegård (MDPI AG, 2020)
Objective: To develop and test a simple medication-focused patient counseling intervention at hospital discharge, with the aim of improving patient satisfaction. Methods: The intervention was developed during a workshop and carried out by pharmaconomists. The final intervention comprised preparing information for the discharge counseling, medication reconciliation, discussion with physician, patient counseling at discharge, medication report to primary care physician, and phone follow-up three days after discharge. The intervention was tested against usual care in a gastrointestinal surgical unit in a feasibility study, using the setup of a randomized controlled trial, with patient satisfaction as the primary outcome. Results: A total of 85 patients were invited to participate in the study. Following refusals (n = 11) and exclusions (n = 10), 32 patients were included in each trial arm (median age of 66.5 years; 52% males; median admission length of seven days). Patient satisfaction was high in both groups, with 75% (intervention) and 91% (control) reporting being overall satisfied with the discharge process (p = 0.10). No other differences between the groups were identified. Conclusions: The intervention did not result in improved patient satisfaction. This is likely attributed to the low number of patients included, the high satisfaction at baseline, and the lack of a validated tool to measure patient satisfaction. The developed intervention and study findings can inform future studies.